Vector Control Methods Adopted By a Village in Andaman & Nicobar Islands: A Cross-Sectional Study - Lena Charlette Stephen; Jahnavi G; Pandurang V Thatkar; Shivani Rao; Bhanu Pratap Singh Gaur; Ajay Raj Sethuraman (Medsci Publications, 2018)
Background and Objectives: In Andaman & Nicobar Islands vec- tor borne diseases are a common public health problem. This study was conducted to assess the vector control methods adopted by households in Wandoor village of South Andaman and to as- sess the coverage of IRS and ITN. Methods: The cross-sectional study was conducted in Wandoor, between January to March 2017. Using systematic sampling, every third house was identified for inclusion in the study. Data was col- lected using a semi structured questionnaire, administered to one respondent per household. Results: Of the 87 households, vector borne diseases were re- ported by five households (5.75%; 95% CI: 1.89 to 12.9, p<0.0001). Almost 97% (95% CI: 90.25 to 99.28, p value<0.0001) of the families used one or other method of vector control measures.The total coverage by IRS of all households was 20.7% (95% CI: 12.7 to 30.7, p<0.001)    and    ITN    use    was    3.4%    (95%    CI:    0.72    to    9.7, p<0.001).Refusal rate to IRS was 66% (95% CI: 51.73 to 78.48, p=0.027). Interpretation: Coverage with IRS and ITN was poor. Personal protection methods were widely used. Most of the cases of VBD in the study occurred in households which use vector control meth- ods other than ITN and IRS.